2013
DOI: 10.4103/1119-3077.113455
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic study of the pterion in Nigerian dry human skulls

Abstract: These findings are important for the surgeon as the pterion junction is a common extracranial landmark in neurosurgical and surgical approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 10 publications
(15 reference statements)
7
14
1
4
Order By: Relevance
“…Lee et al reported the incidence of epipteric type of pterion as 40.5% which is very high compared to present study [14]. Ethnic variation was observed in the location of pterion as the average distance from the center of pterion to mid-point on zygomatic arch was 37.40±3.92 mm in the present study, which was less than that mentioned by the Ukoha et al, and Eboh et al, in Nigerian skulls but similar to that reported by Suchit et al, and Hari Prasad et al, in north Indian skulls [6,16,17,19]. The average distance between the center of pterion to fronozygomatic suture, anterosuperior margin of external auditory meatus and inferior point on mastoid process of the present study were similar to the results of North Indian studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Lee et al reported the incidence of epipteric type of pterion as 40.5% which is very high compared to present study [14]. Ethnic variation was observed in the location of pterion as the average distance from the center of pterion to mid-point on zygomatic arch was 37.40±3.92 mm in the present study, which was less than that mentioned by the Ukoha et al, and Eboh et al, in Nigerian skulls but similar to that reported by Suchit et al, and Hari Prasad et al, in north Indian skulls [6,16,17,19]. The average distance between the center of pterion to fronozygomatic suture, anterosuperior margin of external auditory meatus and inferior point on mastoid process of the present study were similar to the results of North Indian studies.…”
Section: Discussioncontrasting
confidence: 56%
“…The sutural morphology of pterion has been studied in diverse ethnic groups by several authors as shown in table 3 [8][9][10][11][12][13]. Table 3 depicts the comparison of results of the present study with the results of previous studies.…”
Section: Resultssupporting
confidence: 54%
“…Results of current study are in line with Mishra et al 1 and K Epharaim Vikram Rao 2 Mwachaka et al [8] Apinhasmit et al [11] Kumar S. et al [13] Whereas mean values of present study are slightly less than those of Oguz et al [7], Ukohla et al [12] and Eboh and Obaroefe [14].…”
Section: Discussionsupporting
confidence: 46%